Analysis Of The Financial Performance Of Pt Multistrada Arah Sarana Tbk Before And After Debt Restructuring - Paba Folo, Yohana Elisa; Andi Candra, Yudas Tadius (Faculty of Economics dan Business, Atma Jaya Makassar University, 2024)
This study aims to determine the significant differences in the level of liquidity, profitability, and solvency of PT Multistrada Arah Sarana before and after debt restructuring. The results showed that debt restructuring managed to improve the company's liquidity and profitability significantly, but did not have a significant impact on solvency. Significantly, but did not have a significant impact on solvency. Overall, this study concludes that debt restructuring has a positive impact on the company's positive impact on the company's financial performance, especially in terms of its ability to meet short-term to fulfill short-term obligations and generate profits, although it was not followed by an increase in the ability to fulfill long-term obligations. with an increase in the ability to meet long-term obligations. The increase in liquidity and profitability indicate that debt restructuring efforts have succeeded in strengthening the financial position of the company and providing efforts have successfully strengthened the company's financial position and contributed positively to positive contribution to business continuity and future financial performance. The findings of This confirms the benefits of debt restructuring in improving the company's financial performance, especially in the aspects of liquidity and profitability. the company, especially in the aspects of liquidity and profitability